Non-thermal phase separation of P3HT and PCBM using polar aprotic solvents for enhancement of photovoltaic performance in bulk heterojunction solar cells - Lee, Ji-Seon; Kim, BongSoo; Park, Nam-Gyu (ELSEVIER SCIENCE SA, 2013)
Additive-assisted non-thermal phase separation of P3HT and PCBM was studied using nitrile solvents that have low boiling points. 10 volume% of acetonitrile (ACN) or valeronitrile (VN) was added to the P3HT:PCBM blend chlorobezene solution. The P3HT:PCBM bulk heterojunction layer prepared without nitrile solvents showed a power conversion efficiency (PCE) of 0.75%. The ACN addition to the blend solution improved the PCE slightly to 1.07% and the VN addition nearly doubled the PCE to 1.40%. The PCEs were mainly enhanced due to the increased photocurrent density. More specifically, the increased crystallinity and nanoscale phase separation of P3HT chains and PCBM molecules were key reasons for the improvement, which were clearly observed in the UV-visible absorption spectroscopy, atomic force spectroscopy (AFM), and scanning electron microscopy (SEM) experiments. From the normalized UV-visible absorption spectra, the addition of ACN and VN into the P3HT:PCBM blend solution made a red-shift of main absorption peak from 500 to 510 nm with the appearance of pronounced shoulder peaks at 555 and 610 nm. This feature suggested that the interaction between P3HT chains was strengthened with aid of the additives. The main difference between ACN and VN additives was revealed in the AFM and SEM imaging. The VN additive induced to form self-organized 1-dimensional (1D) P3HT domains, which resulted from the fact that the VN consists of longer alkyl chains and have higher boiling point. The interaction between the alkyl chain part in the VN with hexyl chains in the P3HT should promote the nanostructured domain formation of P3HT chains. In addition, the long 1D P3HT domains were web-likely connected, which enabled efficient charge transport in the P3HT:PCBM blend film. Therefore, we concluded the highest photovoltaic performance of VN-assisted P3HT:PCBM blend devices was achieved by the good phase separation and well-connected transporting channel formation in the P3HT:PCBM blend film. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: POLYMER; BLENDS; FILMS; POLY(3-HEXYLTHIOPHENE); MORPHOLOGY; CRYSTALLINITY; ABSORPTION; TRANSPORT; NETWORK